(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The possibility of someone claiming to be a follower of Christ without having sufficient faith, or even any faith at all, is clearly highlighted by Jesus himself in this text under consideration. Hence, his healing of the boy possessed by a demon, after his disciples’ curious inability to do the same, made Jesus to decry the faithlessness and perversity of that generation of his followers as they also faced the imminence of his final departure from this world (Matt 17:17). This led to Jesus’ insistence that for his followers to be meaningfully so, the need for faith, that is even as small as a mustard seed, is imperative (Matt 17:20). This paper aims at a deep study of that text of Matt 17:14-20 so as to bring out, as much as possible, how the behaviour of Jesus’ disciples as well as the injunctions of Jesus therein would be of greater benefit to the Christians of this day and age. The methodology employed in the study is theological-sociological, augmented with the Historical Critical method which is used particularly in the exegesis of that biblical text. All these have helped to throw more light on the mind of Jesus in that text especially, revealing also that the situation of faithlessness, decried by him, seems to be even more pronounced in this day and age, mainly, on account of the rapid developments in science and technology, particularly in the area of communication – otherwise also known as the social media. These advancements, although veritably beneficial to humanity, tend, however, to also precipitate a loss of interest on matters which are not purely scientific, so to speak, especially faith and religion – often leading to the weakening of the faith of many Christians as well as its active practice or even the outright abandonment of the same, especially by the youth. Therefore, this paper recommends that Christians have to go the extra mile in nourishing their faith, especially through its more active and dynamic expression, so as to make it ever relevant to all epochs, including this digital age – the role of Christian leaders in that task being, in the main, indispensable. This, then, leads to the significance of this paper in the emphasis that the knowledge of God and, hence faith in and worship of him in Christianity, for example, actually enhance human dignity instead of undermining or destroying it. Thus, the clear consciousness of this axiom and its application in practice, the author maintains, would naturally lead Christians today, and indeed humankind, to a life of general fulfilment, ultimate balance and equilibrium even amidst the many advancements in science and technology in this day and age.